Structure–Thermodynamic‐Property Relationships in Cyanovinyl‐Based Microporous Polymer Networks for the Future Design of Advanced Carbon Capture Materials. (29th May 2017) - Yassin, Ali; Trunk, Matthias; Czerny, Frank; Fayon, Pierre; Trewin, Abbie; Schmidt, Johannes; Thomas, Arne
Abstract : Nitrogen‐rich solid absorbents, which have been immensely tested for carbon dioxide capture, seem until this date to be without decisive molecular engineering or design rules. Here, a family of cyanovinylene‐based microporous polymers synthesized under metal‐catalyzed conditions is reported as a promising candidate for advanced carbon capture materials. These networks reveal that isosteric heats of CO2 adsorption are directly proportional to the amount of their functional group. Motivated by this finding, polymers produced under base‐catalyzed conditions with tailored quantities of cyanovinyl content confirm the systematical tuning of their sorption enthalpies to reach 40 kJ mol −1 . This value is among the highest reported to date in carbonaceous networks undergoing physisorption. A six‐point‐plot reveals that the structure–thermodynamic‐property relationship is linearly proportional and can thus be perfectly fitted to tailor‐made values prior to experimental measurements. Dynamic simulations show a bowl‐shaped region within which CO2 is able to sit and interact with its conjugated surrounding, while theoretical calculations confirm the increase of binding sites with the increase of PhCC(CN)Ph functionality in a network. This concept presents a distinct method for the future design of carbon dioxide capturing materials. Abstract : Microporous polymer networks with different cyanovinylene contents show that CO2 sorption enthalpies are directly proportional to the quantity of functional groups. As a result, affinities for carbon capture can be engineered to tailor‐made values.